Three scales of professional deviance within organizations - Joseph A. Raelin (Journal of Organizational Behavior, 1994)
Salaried professionals may exhibit organizational deviance when faced with conflict resulting from their mutual role as professional and employee. Some of this behavior may be directly harmful to both the individual and the organization, whereas some may constitute adaptive maladjustments. An earlier study proposed that these deviant behaviors could be organized into Guttman scales. In this article, three such scales were tested for underlying unidimensionality and cumulativeness using scalogram analysis. Not only was the practice of organizational deviance, although not widespread, confirmed, but the scales survived the parameters of the Guttman procedure. A replication of the scales produced sufficient validation for their further development and usage.
Keywords: M12; M53; M54; J44; L84; D24; J24; 650; Professionals; Professional deviance; Scalogram analysis; Deviance; Professional commitment